Salt reduction has no negative effects on the sensorial acceptability of traditional dry-fermented sausages from Alentejo, Portugal - Laranjo, Marta (2014)
The growing demand for traditional food products is associated with health and nutritional concerns. The World Health Organisation recommends daily values of less than 2g of sodium, corresponding to less than 5g NaCl. Low-salt dry-fermented sausages were manufactured using two pig genotypes (Alentejano/Iberian x Duroc), two NaCl concentrations (3%/5%) and two casing calibres (small/large). Three independent batches with replicates were prepared. The effect of genotype, salt content and calibre was studied on the microbiological, physicochemical and textural parameters, as well as on sensory acceptability. Analyses of variance were performed considering genotype, NaCl content and calibre. Both physicochemical parameters (pH and aw) showed similar values to those found in other European dry-fermented meat products. Different numbers of lactic acid bacteria (LAB) were observed between the two salt contents (p<0.05), the LAB number decreasing with the increase in NaCl, which may be explained by the enhanced growth of LAB with higher aw values. Concerning the two salt contents, pH increases with salt content, whereas aw decreases (p<0.05). The Texture Profile Analysis (TPA) revealed significant differences between the two salt contents regarding hardness and chewiness (p<0.05). Concerning the sensorial analysis, the NaCl effect was sensed in the attributes aroma intensity and salt perception (p<0.05). Aromas are more intensely sensed in products with lower salt contents, which might be explained by the enhanced activity of proteolytic and lipolytic enzymes under low NaCl conditions, thus increasing the release of volatile compounds. Furthermore, salt reduction does not negatively affect the quality and acceptability of sausages. Acknowledgements This work was supported by national funds through project PRODER (QREN/PRODER/Medida 4.1) and funded by FEDER Funds through the COMPETE and National Funds through FCT under the Strategic Project PEst-OE/AGR/UI0115/2014. The authors thank PALADARES ALENTEJANOS Lda., A. Oliveira, G. Pias and R. Bicho for their collaboration.